Prostate cancer cell-derived exosomes ZNF667-AS1 reduces TGFBR1 mRNA stability to inhibit Treg expansion and DTX resistance by binding to U2AF1 - Zhenfeng Shi; Wenjing Pu; Min Li; Mierzhayiti Aihemaitijiang; Shuo Li; Xiaoan Zhang; Bide Liu; Min Sun; Jiuzhi Li; Zhiwei Li (BMC, 2024)
Abstract Background Docetaxel (DTX) resistance attenuates anti-tumor effects of DTX on prostate cancer (mCRPC) and drug resistance was related to Treg expansion in tumors. ZNF667-AS1 played a suppressing role in various tumors and tumor-derived exosomes carry lncRNAs to participate in tumor progression. Here, the effects of ZNF667-AS1 on malignant characteristics and DTX resistance in PC and the effect and its underlying molecular mechanism of tumor-derived exosomes carrying ZNF667-AS1 on Treg expansion were investigated. Methods The identification of exosomes were determined using TEM, NTA and western blot. The abundance of genes and proteins were evaluated using IHC, RT-qPCR, western blot and FISH. Malignant phenotypes of PC cells were evaluated by means of Edu, scratch test, transwell, CCK-8 and flow cytometry. The percentage of CD4+CD25+Foxp3+ Tregs was detected using flow cytometry. The location of ZNF667-AS1 was detected using nuclear-cytoplasmic fractionation. The co-location of ZNF667-AS1 and U2AF1 protein was detected using IF-FISH assay. The interactions among ZNF667-AS1, TGFBR1 and U2AF1 were verified using RNA pull-down, RIP and dual luciferase activity. Results ZNF667-AS1 expression in PC samples was lowered, which was negatively relative to poor prognosis and DTX resistance. ZNF667-AS1 overexpression inhibited malignant phenotypes of PC cells, tumor growth and DTX resistance. Besides, DTX resistant cell-derived exosomes expressed lower ZNF667-AS1 expression. Exosomes carrying exogenously high ZNF667-AS1 expression derived PC cells or serum of mice suppressed Treg expansion. On the mechanism, ZNF667-AS1 interacted with U2AF1 to destabilize TGFBR1 mRNA and reduce TGFBR1 expression in CD4+T cells. Conclusion ZNF667-AS1 suppressed cell growth of PC cells, tumor growth of mice and DTX resistance to PC cells and exogenously high ZNF667-AS1 expression in tumor-derived exosomes destabilized TGFBR1 mRNA and reduce TGFBR1 expression through interacting with U2AF1, thus resulting in attenuated Treg expansion, which was related to DTX resistance.